An Environmental Education Learning Model for Early Childhood: Achieving Sustainable Development - Mukhlis, Akhmad; Elvira, Melly; Tegariyani Putri Santoso, Sandy (Al-Athfal: Jurnal Pendidikan Anak, 2024)
Purpose – Educational institutions play a crucial role in addressing environmental problems through Education for Sustainable Development (ESD) for early childhood. This research aims to identify effective methods for implementing sustainable education goals in environmental learning for young children by developing an environmental learning model. Design/methods/approach – This research and development study utilized Borg & Gall's development model, simplified for efficiency in terms of energy, time, and cost. The study focused on the validation stage, with testing and dissemination planned for subsequent research. The product was designed based on an initial needs analysis. Currently, environmental learning is limited to cognitive abilities only, lacking additional skills or habits imparted to the children. The product was validated through a Forum Discussion Group with Jakarta Bisa School and Gaharu Nature School in Bandung. Findings – Validation results indicate that environmental education can begin with character development in children. Jakarta Bisa School can implement the Green Attitude, which embodies values such as Life, Love, Responsibility, the Universe, and Sustainability. Additionally, learning should involve more direct experiences, allowing children to observe the natural life cycle, environmental care, and the sustainability of natural resources. Research implications/limitations – This research requires an extended period for designing and implementing the environmental learning model. By involving multiple stakeholders, it has the potential to change teachers' and parents' perceptions in educating early childhood. Practical implications – Environmental learning is essential for fostering future change. Children will grow with a strong understanding of the importance of love and care for the universe and a sense of responsibility for life within it. This approach helps cultivate environmentally conscious individuals who are equipped to address global challenges and contribute to a sustainable future. Originality/value – This research contributes to the field of education by promoting a better future through learning aligned with ESD goals. It provides innovative teaching methods and materials that foster environmental awareness and sustainability from an early age. Paper type Research Paper